Cognitive flexibility predicts early reading skills - Colé, Pascale; Duncan, Lynne G.; Blaye, Agnès (Frontiers in Psychology, 2014)
An important aspect of learning to read is efficiency in accessing different kinds of linguistic information (orthographic, phonological, and semantic) about written words. The present study investigates whether, in addition to the integrity of such linguistic skills, early progress in reading may require a degree of cognitive flexibility in order to manage the coordination of this information effectively. Our study will look for evidence of a link between flexibility and both word reading and passage reading comprehension, and examine whether any such link involves domain-general or reading-specific flexibility. As the only previous support for a predictive relationship between flexibility and early reading comes from studies of reading comprehension in the opaque English orthography, another possibility is that this relationship may be largely orthography-dependent, only coming into play when mappings between representations are complex and polyvalent. To investigate these questions, 60 second-graders learning to read the more transparent French orthography were presented with two multiple classification tasks involving reading-specific cognitive flexibility (based on words) and non-specific flexibility (based on pictures). Reading skills were assessed by word reading, pseudo-word decoding, and passage reading comprehension measures. Flexibility was found to contribute significant unique variance to passage reading comprehension even in the less opaque French orthography. More interestingly, the data also show that flexibility is critical in accounting for one of the core components of reading comprehension, namely, the reading of words in isolation. Finally, the results constrain the debate over whether flexibility has to be reading-specific to be critically involved in reading.